2015
DOI: 10.1007/s10096-015-2405-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of fusarioses in a university hospital in Turkey during a 20-year period

Abstract: Fusarium species have started appearing increasingly as the main cause of infections, particularly in immunocompromised patients. In this study, we aimed to present the first epidemiological data from Turkey, analyze fusariosis cases that have been monitored in a university hospital during the past 20 years, identify the responsible Fusarium species, and determine antifungal susceptibilities. A total of 47 cases of fusariosis was included in the study. Fusarium isolates were identified by multilocus sequence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 35 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…In vitro antifungal susceptibility profiles of Fusarium species demonstrate high MICs to most antifungal agents [ 10 , 11 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Notably, some species may exhibit different patterns of susceptibility: F. solani species complex are usually resistant to azoles and exhibit higher amphotericin B MIC values than other species, whereas F. oxysporum and F. verticilloides may be susceptible to voriconazole and posaconazole [ 10 , 11 , 55 ].…”
Section: Eucast Vs Clsimentioning
confidence: 99%
“…In vitro antifungal susceptibility profiles of Fusarium species demonstrate high MICs to most antifungal agents [ 10 , 11 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Notably, some species may exhibit different patterns of susceptibility: F. solani species complex are usually resistant to azoles and exhibit higher amphotericin B MIC values than other species, whereas F. oxysporum and F. verticilloides may be susceptible to voriconazole and posaconazole [ 10 , 11 , 55 ].…”
Section: Eucast Vs Clsimentioning
confidence: 99%
“…In general, a prevalence of Fusarium in dermatological infections has been reported to range between 2 and 8 % [6][7][8], but this is particularly higher in Colombia, being estimated at 15-30 % [9][10][11][12][13]. In two studies, conducted in 2003 and 2009 in Medellín and Bogotá, respectively, Fusarium solani was the most frequent cause of onychomycosis, followed by Fusarium oxysporum and Fusarium verticillioides [14,15], although the distribution of Fusarium species in dermatological infections varies around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Most published studies have focused on prevalence in single healthcare centers. 10, 11, 12, 13, 14, 15, 16 Nucci et al 17 reported 233 cases from different hospitals on a global scale. Mohammed et al 18 reported 26 cases from the United States and reviewed 97 cases from the literature, and Horn et al 12 described 65 cases from the North American Path Alliance Registry.…”
Section: Introductionmentioning
confidence: 99%